2015
DOI: 10.2147/cpaa.s82143
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic equivalence study of two formulations of the anticonvulsant pregabalin

Abstract: PurposeThe present study was conducted to evaluate whether the bioavailability of pregabalin capsules 150 mg manufactured by PT Dexa Medica was equivalent to the reference formulation.MethodsThis was a randomized, open-label, two-period, two-sequence, and crossover study under fasting condition, with a 1-week washout period. Plasma concentrations of pregabalin from 20 subjects were determined by using a validated liquid chromatography with tandem mass spectrometry (LC-MS/MS) detection method. Pharmacokinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…With this concept, drug regulators require that generic formulations should have equivalent clinical effects with its innovator counterparts, resulting in interchangeability of both products. In compliance with the requirement, we have also conducted bioequivalence studies on several generic formulations [21,22,23,24]. Our current study on pramipexole was carried out with the same requirements in mind.…”
Section: Discussionmentioning
confidence: 99%
“…With this concept, drug regulators require that generic formulations should have equivalent clinical effects with its innovator counterparts, resulting in interchangeability of both products. In compliance with the requirement, we have also conducted bioequivalence studies on several generic formulations [21,22,23,24]. Our current study on pramipexole was carried out with the same requirements in mind.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic parameters of an orally administered single dose of a PREG capsule of 150 mg revealed that C max was 3.99 ng/L, AUC was 28.31 ng/mL x h, T max was 1.00 h and T 1/2 was 5.66 h [87] . The kinetics of PREG showed linear features (proportional to the dosage up to 900 mg per day) [88] .…”
Section: Its Chemical Structure Is (S)-3-(aminomethyl)-5-methylhexanomentioning
confidence: 99%
“…The average fatal dose of pregabalin was found to be different centrally (54.1 mg/L) and peripherally (45.3, and 206.7 mg/L). Even in some non-fatal pregabalin overdose cases the serum concentration of this drug was found to be varied depending upon the condition of the person such as 20.8 mg/L was found when a person is drowsy but with no toxic symptoms founds, 60 mg/L was found after 24 hours of the pregabalin ingestion and 66.5 mg/L was found at the time of coma [16][17][18][19][20].…”
Section: The Abuse Of Pregabalinmentioning
confidence: 99%